2014
DOI: 10.2136/sssaj2013.08.0322nafsc
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Soil Moisture Patterns in a Northern Minnesota Forest

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher. Long-Term Soil Moisture Patterns in a Northern Minnesota Forest North American Forest Soils Conference Proceedings S oil moisture influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Regardless, if the decrease in soil moisture observed in response to increasing temperatures over the last century continues (Dymond et al. ), our results suggest the importance and intensity of crowding to individual tree growth may increase in the future, which has implications for forest management.…”
Section: Discussionmentioning
confidence: 69%
“…Regardless, if the decrease in soil moisture observed in response to increasing temperatures over the last century continues (Dymond et al. ), our results suggest the importance and intensity of crowding to individual tree growth may increase in the future, which has implications for forest management.…”
Section: Discussionmentioning
confidence: 69%
“…More recently, studies have shown that the linkage between climate and tree growth is dynamic over time, with periods of increased stress on trees following drought or insect outbreaks (Itter, Finley, D'Amato, Foster, & Bradford, ). Given increasing temperatures and decreasing soil moisture levels at the MEF (Dymond et al, ), plant‐available water levels may drop even further in the region. An increase in dry periods and thus low water availability could have profound impacts on ecosystem productivity and health in the region (Briggs & Knapp, ; Graumlich, ).…”
Section: Discussionmentioning
confidence: 99%
“…Percent volumetric soil moisture was measured using a Troxler Series 4300 neutron probe moisture gauge (Troxler Electronic Laboratories, Inc., Research Triangle Park, North Carolina, USA) at a network of 27 sites across the MEF. The neutron probe technique was chosen so new soil moisture measurements could be compared with historical soil moisture records at the MEF that date back to 1966 (Dymond et al, , ; Sebestyen et al, ). These historical monitoring sites are predominately located in ridge aspen stands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water level data were recorded daily using Belfort model FW‐1 strip chart recorders with float and pulley systems. Total annual precipitation has not changed over the course of the 50‐year study period, although mean annual temperature has increased approximately 2.3°C from 1966 to 2012 (Figure ; Dymond et al, ). Monthly potential ET, or PET, was calculated at the MEF using the Thornthwaite method (Thornthwaite & Mather, ), and monthly changes in moisture were quantified using a cumulative moisture index (CMI), where CMI is equal to precipitation less PET (Hogg, ).…”
Section: Methodsmentioning
confidence: 98%